Analisis Gerusan Lokal Di Hilir Bed Protection = Local Scour Analysis in Downstream Bed Protection - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Bed protection is often used to reduce scouring of river and reducing its scraping hole which bring some risks toward structure stability where it is situated far from bulidings. Bed protection is failed when it changed geometrically. Bed protection failure influences structure stability indirectly. However, bed protection instability that is influenced by upstream scour slope, reduces structure foundation energy. The upstream scour causes water construction failures. Therefore it needs more study about local scouring of river water phenomenon in bed protection downstream. In this research, the two kinds of models were used : empty apron and energy breaker, such as chute block and end sill. Both of these models are tested experimentally with in flow discharge and bed protection length variations. Local scouring of river water is watched closely jespecially scour depth, maximum scour position, and scour length) and flow parameter influenced toward scour of each model. The result showed that longer protection caused less scour. Apron model using chute block and end sill produced less scour compared to empty apron model for different bed protection length. Chute block and end sill model give scour dept reduction of 11,74 %. Using dimensional analysis, gave empirical equation with bed protection length parameter for each model.